2017
DOI: 10.7150/oncm.17910
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Capecitabine and Radiation Therapy for High-risk Primary Breast Cancer

Abstract: Introduction: Data is limited for concurrent capecitabine-radiotherapy (CCRT) in primary breast cancer. We evaluated outcomes and toxicities of patients at high risk of locoregional recurrence receiving adjuvant CCRT. Methods: Ten non-metastatic breast cancer patients receiving concurrent treatment were reviewed retrospectively. Capecitabine was given during and after radiation. Toxicity was reviewed using weekly on-treatment visit and follow-up notes. Results: All patients had stage II-III disease. Four patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…Skin fibrosis G1 was observed in 12.5% of our patients in our study, and the DFS was 62.5% in patients with tumor stage III, which is inconsistent with Goyal et al 24 , in which skin fibrosis was reported in 22.2% of cases, and the 2 year distant recurrence free survival (DRFS) was 75%; this difference can be explained by our study's longer follow up.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Skin fibrosis G1 was observed in 12.5% of our patients in our study, and the DFS was 62.5% in patients with tumor stage III, which is inconsistent with Goyal et al 24 , in which skin fibrosis was reported in 22.2% of cases, and the 2 year distant recurrence free survival (DRFS) was 75%; this difference can be explained by our study's longer follow up.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, no cases developed LRR during the follow-up period, and 6 patients developed distant metastases (15%), which is consistent with the results of Alhanafy et al in which 6 patients (12%) developed distant metastases (12%) and one patient developed LRR during the 2 year follow-up period 26 , while in Panoff et al 4 patients (20%) developed distant metastases and no LRR was documented 24 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations